2009
DOI: 10.1095/biolreprod.108.073924
|View full text |Cite
|
Sign up to set email alerts
|

Participation of the Human Sperm Proteasome in the Capacitation Process and Its Regulation by Protein Kinase A and Tyrosine Kinase1

Abstract: The proteasome is a multicatalytic cellular complex present in human sperm that plays a significant role during several steps of mammalian fertilization. Here, we present evidence that the proteasome is involved in human sperm capacitation. Aliquots of highly motile sperm were incubated with proteasome inhibitors MG132 or epoxomicin. The percentage of capacitated sperm, the chymotrypsin-like activity of the proteasome, cAMP content, and the pattern of protein phosphorylation were assayed by using the chlortetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(58 citation statements)
references
References 82 publications
3
52
0
3
Order By: Relevance
“…Sawada et al reported that in marine invertebrate such as ascidians and sea urchins, sperm proteasomes is responsible for sperm penetration of the vitelline envelope, and the proteasome is a lytic agent called lysin, which is essential for disintegration of the egg extracellular matrix (Sawada et al 2002a, Sakai et al 2003, Yokota & Sawada 2007a. A similar conclusion was drawn from mammalian fertilization, including that in mice, pigs, and man (Pasten et al 2005, Kong et al 2009, Zimmerman et al 2011.…”
Section: Introductionmentioning
confidence: 84%
“…Sawada et al reported that in marine invertebrate such as ascidians and sea urchins, sperm proteasomes is responsible for sperm penetration of the vitelline envelope, and the proteasome is a lytic agent called lysin, which is essential for disintegration of the egg extracellular matrix (Sawada et al 2002a, Sakai et al 2003, Yokota & Sawada 2007a. A similar conclusion was drawn from mammalian fertilization, including that in mice, pigs, and man (Pasten et al 2005, Kong et al 2009, Zimmerman et al 2011.…”
Section: Introductionmentioning
confidence: 84%
“…Proteasomal ubiquitin-dependent epididymal protein degradation is important for spermatogenesis [84], fertilization [85][86][87], and removal of DNA-damaged spermatozoa [88]. Furthermore, the response to unfolded proteins not only includes the protein refolding, a function conserved between the Low and High groups, but also the degradation of unfolded proteins by the ubiquitin system [89].…”
Section: Enriched Functions In the Low Sperm Dna Fragmentation Groupmentioning
confidence: 99%
“…For example, multi-enzymatic sperm protease complexes with similar sedimentation coeffi cients as purifi ed proteasomes from other tissues have been isolated from mouse (Pasten et al 2005 ), pig (Zimmerman and Sutovsky 2009 ), and human (Morales et al 2003 ;Morales et al 2004 ;Baker et al 2007 ) spermatozoa. Accordingly, the substrate-specifi c enzymatic activities (trypsinlike, chymotrypsin-like, and peptidylglutamyl peptide-hydrolyzing activities) of these sperm proteasomes have been recorded in mice (Pasten et al 2005 ;Bedard et al 2011 ;Rivkin et al 2009 ), pigs (Sutovsky et al 2004 ;Yi et al 2007a ;Yi et al 2009 ), and humans (Morales et al 2003;Chakravarty et al 2008 ;Kong et al 2009 ).…”
Section: Proteasome Localization and Activity In Mammalian Spermatozoamentioning
confidence: 99%
“…Then, the intracellular and extracellular proteasomes would blend into the acrosomal shroud and participate during the AE. Sperm proteasomes have been shown to be essential for acrosomal function and sperm-zona penetration during fertilization in several mammalian species such as mouse, pig, and human (Pasten et al 2005 ;Kong et al 2009 ;Zimmerman et al 2011 ). It is possible that the proteasomes modulating these cellular events could participate in other steps of fertilization as well.…”
Section: Proteasome Localization and Activity In Mammalian Spermatozoamentioning
confidence: 99%